The Effect of Consumer Ethnocentrism, Brand Image, and Perceived Quality,on Purchase Decisions With Purchase Intention as Intervening Variable - Haikal, Dziqry Muhammad (Jurnal Akuntansi, Manajemen dan Ekonomi, 2018)
The purpose of this research is to know and analyze the effect of consumer ethnocentrism, brand image, and perceivedquality of Eiger outdoor equipment product to consumer purchase decision, and to test purchase intention as intervening variable between consumer ethnocentrism ,brand image, and perceivedquality effect the purchase decision. The sample in this study there are 180 respondents who are users of Eiger products in Tasikmalaya region. Convenience sampling method is used in the determination of this research sample. Data were analyzed using Structural Equational Modeling (SEM) with SPSS and AMOS statistical software. The results of this study show that. Consumer ethnocentrism has a positive but no significant effect on purchase decisions. Brand image has a positive but no significant effect on purchase decisions. Perceived quality have a positive effect on purchase decisions. Purchases intention have a positive effect on purchase decisions. Consumer ethnocentrism positively effects purchase decisions with purchase intention as intervening variable. Brand image positively effects purchase decisions with purchase intention as intervening variable. Perceived quality positively effect purchase decisions with purchase intention as intervening variable.